Vagueness Facilitates Search - van Deemter, Kees (Proceedings of the Amsterdam Colloquium, 2009)
This paper addresses the question why language is vague. A novel answer to this question is proposed, which complements other answers suggested in the literature. It claims that vagueness can facilitate search, particularly in quasi-continuous domains (such as physical size, colour, temperature), given that different speakers are likely to attach subtly different meanings to words (such as “tall”, “blue”, “hot”) defined over such domains.